2004
DOI: 10.1039/b316759c
|View full text |Cite
|
Sign up to set email alerts
|

A novel azulene synthesis from the Ramirez ylide involving two different modes of its reaction with activated alkynes

Abstract: The Ramirez ylide undergoes electrophilic substitution with acetylenedicarboxylates to form Z and E adducts. The latter can react by cycloaddition with another equivalent of the alkyne to provide a new route to novel tetra-substituted azulenes, which show interesting bond localisation and crystal packing effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…We found that by variation of the reaction conditions the Friedel-Crafts phosphorylation of FcH with aromatic Ph 2 PCl 1d 16 can be also applied for dialkylchlorophosphines R 2 PCl (R = Me, n Bu, n Hex). Based on 31 P NMR monitoring of the conversion of ferrocene with n Bu 2 PCl 1b and AlCl 3 a reaction pathway is proposed (Scheme 2).…”
Section: Synthesis Of Dialkylferrocenylphosphines 2a-cmentioning
confidence: 99%
“…We found that by variation of the reaction conditions the Friedel-Crafts phosphorylation of FcH with aromatic Ph 2 PCl 1d 16 can be also applied for dialkylchlorophosphines R 2 PCl (R = Me, n Bu, n Hex). Based on 31 P NMR monitoring of the conversion of ferrocene with n Bu 2 PCl 1b and AlCl 3 a reaction pathway is proposed (Scheme 2).…”
Section: Synthesis Of Dialkylferrocenylphosphines 2a-cmentioning
confidence: 99%
“…Theo nly previously reported cyclopentadienide-containing species were cyclopentadienylidenephosphorane,a lso known as Ramirez ylides (57,F igure 3). [31] Theheterolytic cleavage of carbon-carbon bonds to form ac arbocation/carbanion pair is often unfavored, hence carbanions are not often observed in the role of leaving groups.T his is due to the lack of ad ipole in carbon-carbon bonds and the insufficient stabilization of the resulting carbanions. [31] Theheterolytic cleavage of carbon-carbon bonds to form ac arbocation/carbanion pair is often unfavored, hence carbanions are not often observed in the role of leaving groups.T his is due to the lack of ad ipole in carbon-carbon bonds and the insufficient stabilization of the resulting carbanions.…”
Section: Reactions Promoted By Cyclopentadienide Ionsmentioning
confidence: 99%
“…[29] Although better known for their chemical inactivity in Wittig-type reactions,b ecause of their stable zwitterionic structures,Ramirez ylides have been used for electrophilic substitution reactions on the fivemembered ring [30] as well as in cycloaddition reactions. [31] Theheterolytic cleavage of carbon-carbon bonds to form ac arbocation/carbanion pair is often unfavored, hence carbanions are not often observed in the role of leaving groups.T his is due to the lack of ad ipole in carbon-carbon bonds and the insufficient stabilization of the resulting carbanions. [32] However,i ft he corresponding carbanion is stabilized, it may function as agood leaving group.Asuitable system for this would be the aromatic cyclopentadienide ion, whose stability could be further enhanced with electronwithdrawing substitutuents on the ring.…”
Section: Reactions Promoted By Cyclopentadienide Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Über die Verwendung des Cyclopentadienidions zur Vermittlung organischer Reaktionen ist jedoch wenig bekannt. Vor den in hier vorgestellten Arbeiten wurden lediglich Cyclopentadienylidenphosphorane, die auch als Ramirez‐Ylide ( 57 ) bezeichnet werden (Abbildung ), für elektrophile Substitutionen am Fünfring sowie in Cycloadditionen verwendet, obgleich sie aufgrund ihrer stabilen zwitterionischen Strukturen keine Wittig‐Reaktionen eingehen.…”
Section: Durch Cyclopentadienidionen Vermittelte Reaktionenunclassified